Long‐term joint outcomes of regular low‐dose prophylaxis in Chinese children with severe haemophilia A. Issue 2 (6th February 2021) - Wu, Yuefang; Lu, Jingjing; Zhou, Yin; Li, Kuixing; Liu, Ying; Liu, Shufen; Li, Zhuo; zhao, Yongqiang; Poon, Man‐Chiu; Xiao, Juan
Abstract: Objectives: To explore the long‐term joint outcomes of low‐dose prophylaxis in Chinese children with severe haemophilia A and to analyse their related factors. Methods: We retrospectively analysed follow‐up data from 21 severe haemophilia A children on regular low‐dose prophylaxis for 6–10 years. We used International Prophylaxis Study Group magnetic resonance imaging score (IPSG MRI score), Hemophilia Joint Health Score (HJHS), number of target joints, and Hemophilia‐Specific Quality of Life Index (Haemo‐QoL) to evaluate joint outcomes. Factors associated with these outcomes were evaluated by statistical analysis. Results: (1) The children were 1.75 to 17 years age at prophylaxis initiation. Median prophylactic factor VIII dose was 22.9 IU/kg per week. (2) At the end of follow‐up: (a) The total IPSG MRI scores were 2–24 with 90.5% children exhibiting moderate to severe joint involvement (score 7–24); (b) The HJHS ranged 2–27, with 0–10 for 46.7% children and >10 for 53.3% children. There was a positive correlation between the MRI score and HJHS ( p < .05); (c) Compared to their on‐demand treatment period before prophylaxis, target joints numbers decreased, and no child needed auxiliary devices to walk; (d) Joint outcomes were positively correlated with the age at initiation of low‐dose prophylaxis ( p < .05) and negatively correlated with the treatment dose. Conclusion: Long‐term low‐dose prophylaxis had positive effect on joint outcomes compared with on‐demand treatment. However, a certain degree of joint damage remained in all children indicating the need for improving the current strategy of low‐dose prophylaxis.